Періодика литовської етнології в перспективі розвитку науки - Паукштіте-Шакнене, Р. (Народна творчість та етнологія, 2011)
The article discusses how the development of Lithuania‘s science of ethnology was reflected in periodical press. The author analyses publications of three periods, i.e. interwar and Soviet periods, and the period after 1990.